Հայաստանում տարածված ճակնդեղի գենետիկական բազմազանության ուսումնասիրությունը ISSR մարկերների կիրառմամբ - Ալոյան, Տ. Բ.; Բադալյան, Մ. Վ.; Մելիքյան, Ա. Շ. (ՀԱԱՀ հիմնադրամ)
В настоящее время для генетической характеристики различных сортов сельскохозяйственных культур и дикорастущих видов широко используется ISSR-маркирование, или анализ межмикросателлитных сегментов. Цель исследования – паспортизация распространенных в Армении диких видов и популяционных сортов свеклы с использованием ДНК-маркеров для предоставления селекционного материала. Согласно показателям генетического разнообразия, изученные дикие виды и большинство популяционных сортов свеклы представляют собой базовые или типичные генофонды с минимальным количеством и частотой редких аллелей. Genetic markers for the study of genetic diversity are divided into 4 groups: morphological or phenotypic, biochemical or protein, cytogenetic, and molecular or DNA. Currently, ISSR-DNA markers or Inter Simple Sequence Repeats is widely used for the genetic characterization of various crop varieties and wild species. In the present day, ISSR-DNA markers (Inter Simple Sequence Repeats) are widely used to characterize various crop varieties and wild species from their genetic makeup. It is used both for inter-species and intra-species genetic variability of populations and for genetic diversity, and species identification, as well as for genome mapping and marking of useful economic traits. The purpose of this research was to certify the wild species and population varieties of beet common in Armenia using DNA markers, to offer them as a selection starting material. The studied wild species and population varieties of beet are distinguished by a high degree of polymorphism: 33.3-88.9 %. According to the indicators of genetic diversity, most of the studied species and varieties are characterized as the main or typical gene pools with a minimum number and frequency of rare alleles. An exception is the Aparan population of table beet, which is distinguished by a high degree of originality. According to the indicators studied with ISSR DNA markers, it is possible to select the right parental forms for beet breeding activities.
Keywords: Ագրոնոմիա և ագրոէկոլոգիա